Mariculture industry in Malaysia - Mohd. Mazlan Jusoh (Maritime Institute of Malaysia, 1997)
This paper presents the status of the mariculture industry in Malaysia from 1990 to 1997. The major mariculture systems consist of (1) Cockle culture, (2) Mussel culture, (3) Oyster culture, (4) Brackishwater pond culture and (5) Brackishwater cage culture. Cockle culture is still the dominant contributor in terms of tonnage, constituting 88% of mariculture product. In terms of value,brackishwater pond contributed the greatest income for mariculture industry. High debated issues such as loss of mangrove habitat, chemical effluent from mariculture site, indiscriminate use of antibiotics, and the adverse impact of anti-fouling are focussed. The issues of genetic manipulated species and exotic species are also highlighted. The discussion will match the policies and legislations which are being referred to as guidelines. [Author's abstract]